MNGI-17. THE ROAM / EORTC 1308 INFORMATION STUDY RESULTS: HOW QUALITATIVE RESEARCH METHODS CAN OPTIMISE PATIENT RECRUITMENT FOR MENINGIOMA TRIALS. (5th November 2018) - Jenkinson, Michael; Sherratt, Frances; Haylock, Brian; Weber, Damien; Young, Bridget
Abstract: BACKGROUND: ROAM/1308 is an international randomised controlled phase III trial comparing radiation to observation following complete surgical resection of atypical meningioma. We embedded a qualitative sub-study within ROAM/1308 with the aim of optimising patient recruitment. METHODS: Patients approached to participate in the ROAM trial and recruiting clinicians were enrolled into the qualitative sub-study in 11 UK sites. Audio-recorded recruitment consultation (n=30), and semi-structured interviews with clinicians (n=17) and patients (n=23), including decliners and consenters. Analysis of transcribed audio-recordings was informed by content and thematic analysis. Ethics approval was granted for the study. RESULTS: Analysis identified areas where communication was problematic. Giving patients their pathology results immediately before discussing ROAM left them overwhelmed and unable to absorb trial information. Clinicians presentation of the trial arms often lacked balance with a tendency to emphasise the positive aspects of active monitoring (i.e. no additional treatment) while the negative aspects of tumour recurrence were rarely discussed. Conversely the negative aspects of radiotherapy were emphasised whilst neglecting to discuss that radiotherapy may confer better disease control. Patients exhibited bias against radiotherapy citing concerns about side effects, and this perception was rarely challenged by recruiting clinicians. Several patients viewed the prospect of radiotherapy as illogical, in part, due to earlier conversations with neurosurgeons who indicated further treatment was unnecessary following resection. CONCLUSIONS: Embedded qualitative studies can address barriers to recruitment in meningioma trials. The patient information leaflet has been amended and a patient-facing video added to the trial website. Workshops and a webinar for healthcare professionals (surgeons, oncologists research nurses) to enhance communication about ROAM/1308 have been conducted. Subsequent recruitment consultations had a more balanced discussion and clinicians felt more confident approaching patients about ROAM/1308. Ongoing support will be provided to sites to assist them in implementing and maintaining changes in the recruitment consultation.